Top 100 cited classical articles in sentinel lymph nodes biopsy for breast cancer - Liang, Xinrui; Wang, Yu; Fu, Guanghua; Fan, Pingmig; Ma, Ke; Cao, Xu-Chen; Lin, Guang-Xun; Zheng, Wu-ping; Lyu, Peng-fei (Frontiers in Oncology, 2023)
The sentinel lymph node biopsy (SLNB) takes on a critical significance in breast cancer surgery since it is the gold standard for assessing axillary lymph node (ALN) metastasis and determining whether to perform axillary lymph node dissection (ALND). A bibliometric analysis is beneficial to visualize characteristics and hotspots in the field of sentinel lymph nodes (SLNs), and it is conducive to summarizing the important themes in the field to provide more insights into SLNs and facilitate the management of SLNs.: Search terms relating to SLNs were aggregated and searched in the Web of Science core collection database to identify the top 100 most cited articles. Bibliometric tools were employed to identify and analyze publications for annual article volume, authors, countries, institutions, keywords, as well as hotspot topics. Results: The period was from 1998 to 2018. The total number of citations ranged from 160 to 1925. LANCET ONCOLOGY and JAMA-JOURNAL OF THE AMERICAN MEDICAL ASSOCIATION were the top two journals in which the above articles were published. Giuliano, AE was the author with the highest number of articles in this field with 15. EUROPEAN INST ONCOL is the institution with the highest number of publications, with 35 articles. Hotspots include the following 4 topics, false-negative SLNs after neoadjuvant chemotherapy; prediction of metastatic SLNs; quality of life and postoperative complications; and lymphography of SLNs.This study applies bibliometric tools to analyze the most influential literature, the top 100 cited articles in the field of SLNB, to provide researchers and physicians with research priorities and hotspots.